Assessment of left ventricular systolic and diastolic functions in severely malnourished children - Gihan M. Bebars; Hany T. Askalany (SpringerOpen, 2019)
Abstract Background Malnourished children endure many changes in body composition and lose heart and skeletal muscle mass. Diastolic dysfunction is one of the major causes of heart failure with preserved ejection fraction. Aim To assess left ventricular systolic and diastolic functions in children with severe acute malnutrition using tissue Doppler imaging technique and to evaluate the effect of nutritional rehabilitation. Patients and Methods A follow-up case-control study conducted on 60 severely malnourished children (WHZ < -3SD) and 120 age and sex-matched healthy children as a control group. Tissue Doppler imaging (TDI) was done for all included malnourished children at admission and for control to measure left ventricular systolic and diastolic functions. Nutritional rehabilitation was done according to WHO protocol and tissue doppler was repeated after rehabilitation when (WHZ > -2SD) to detect any changes in systolic or diastolic functions. Results Systolic function was normal in malnourished children and control. Grade I diastolic dysfunction was detected in 40% and grade II in 30% of severely malnourished children in comparison to 100% normal diastolic function in control group. No correlations between diastolic dysfunction and either anthropometric measurements, electrolyte disturbances or Hb% in malnourished children before nutritional rehabilitation. Mortality from sepsis with associated ventricular dysfunction grade II documented in 3.3% of malnourished children. After nutritional rehabilitation diastolic function improved significantly as 65.6% of children attained normal diastolic function, 31% grade1 and 3.4% grade II. Positive correlations between diastolic function and WAZ, HAZ, WHZ and MUAC after rehabilitation. Conclusion Severe acute malnutrition affects diastolic function in children which is reversible in most of these cases with rehabilitation. TDI is an easy and practical method for detection and follow-up of ventricular function in malnourished children.